MANIPULATION OF SOCIAL CONSIOUSNESS AS A TECHNOLOGY OF INFORMATION WARFARE - Младьонова, О. Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The purposes and informational psychological influence of social consciousness manipulation as a technology for carrying out warfare are considered. Components of various manipulative methods that influence on mass consciousness are determined. Some techniques and forms of manipulative influence are analyzed.